Industrial Development and Trade Liberalization in Nigeria: Is There a Significant Correlation? - UMORU, David; EBOREIME, Matthew I (Asian Journal of Empirical Research, 2013)
This study investigates the relation between trade liberalization and industrial development in Nigeria. Adopted in the study is the human capital model of endogenous growth with modifications for trade liberalization within the Nigerian context. In the empirical investigation, co-integration and error correction estimation approaches were carried out with the aid of the Generalized Method of Moments [GMM] estimator. A unique co-integration between industrial development and the explanatory variables in the study is found. In order to determine the short-run dynamics around the equilibrium relationship, we estimated an error correction model [ECM]. The empirical findings in this study have it that there is a positive and significant correlation between trade liberalization and industrial development in Nigeria, structural deregulation had positive impact on industrial development in Nigeria, Nigerian industries are labour intensive, industrial production responded negatively and insignificantly to capital formation in Nigeria, industrial development is cumulative and self-sustaining in Nigeria. The result however does not provide evidence of significance of structural deregulation over the period of short-run analysis. The results of the study suggest the need for government to embark on comprehensive implementation of trade liberalization policies in order to accelerate and sustain industrial development in Nigeria. However, the implementation of trade liberalization polices should be gradual.